Analytical solution for transient one-dimensional couette flow considering constant and time-dependent pressure gradients - Zevallos, Andrés Mendiburu [UNESP]; Carrocci, Luiz Roberto [UNESP]; Carvalho Júnior, Joao Andrade de [UNESP] (My University, 2011)
This paperaims to determine the velocity profile, in transient state, for a parallel incompressible flow known as Couette flow. The Navier-Stokes equations were applied upon this flow. Analytical solutions, based in Fourier series and integral transforms, were obtained for the one-dimensional transient Couette flow, taking into account constant and time-dependent pressure gradients acting on the fluid since the same instant when the plate starts it´s movement. Taking advantage of the orthogonality and superposition properties solutions were foundfor both considered cases. Considering a time-dependent pressure gradient, it was found a general solution for the Couette flow for a particular time function. It was found that the solution for a time-dependent pressure gradient includes the solutions for a zero pressure gradient and for a constant pressure gradient.
Keywords: Couette flow; Transient; Parallel plates; Incompressible fluid